KORELASI FENOTYPE DAN HASIL JAGUNG MANIS (Zea mays saccharata, Sturt) DI KECAMATAN RUMBAI PEKANBARU - SURTINAH SURTINAH (Universitas Lancang Kuning, 2018)
The purpose of this research is to know the relationship between vegetative growth with sweet corn produced in experimental garden of Faculty of Agriculture Unilak. The environmental design used was a complete randomized design with 20 replications. Data analysis using correlation analysis. The parameters observed were plant height, leaf number, leaf length, leaf width, weight of cob weighing, cob weight without cornhusk, length of cob weighing, length of cob without cornhusk. The results showed that plant height, leaf number, and leaf width were significantly correlated with unbalanced cob weight, and correlated significantly with the length of cobs weighing and length of cobs without cornhusk. Plant height, leaf number, and leaf width did not give a significant correlation to the weight of cobs weighing. Weight of cobs weighing with unobstructed weight of cobs without real correlated weight, and long cobs without weight with weightlessness showed no real correlation.